Español - Mendez Criollo, María Estefani (2022)
Introduction: The COVID-19 pandemic shocked the world population causing changes in eating habits, food purchase and consumption, physical activity, emotional state, among others, due to the economic impact and the measures applied to prevent the virus's spread. Objective: To analyze the adult's perception about the food purchase, consumption, and preparation, practiced after the confinement by the COVID-19 pandemic. Methods: An exploratory qualitative study was carried out. Twenty adults from the urban and rural areas of Cuenca participated. Semi-structured interviews were conducted until saturation. They were transcribed verbatim and analyzed manually. Results: Food purchase and consumption have changed from the confinement due to the COVID-19 pandemic. All participants indicated that they had difficulty accessing food due to their low purchasing power. Participants from rural areas had access to natural foods of their own crops. Conclusions: The participants in general had difficulties accessing food with good nutritional quality, which could worsen the situation of food insecurity that existed in Ecuador before the Pandemic. More studies are necessary to generate strategies focused on improving the food situation of the population at the local and national levels.